Professional practice in a Psychosocial Care Center: Scientific production in graduate studies (Research, Society and Development, 2021)
Objective: The study aims to understand and analyze the trend of Brazilian scientific productions on professional practice in Psychosocial Care Centers (CAPS). Method: This is a narrative review of the literature, carried out on Capes' theses and dissertations portal, in July 2020. The words used in the search were: [profissona *] AND [practical] AND [CAPS] OR [ psychosocial care center], employing a Boolean operator “AND” or “OR” between them. Results: 217 theses and dissertations were found. From the result of this search, the abstracts were read and after applying inclusion and exclusion criteria, 18 dissertations and 2 theses remained. The analysis of the 20 productions, in full, took place through Bardin's content analysis. The themes that emerged from the established productions were: Mental health care and professional practice in mental health care. Conclusion: It is concluded that the qualitative approach is frequent in theses and dissertations on the theme and that research is needed to qualify the practice of professionals within the CAPS and in mental health in general.